Enhanced hyperspectral image classification for coastal wetlands using a hybrid CNN-transformer approach with cross-attention mechanism - Li, Zhongmei; Liu, Tang; Lu, Yuxiang; Tian, Jing; Zhang, Meng; Zhou, Chenghu (Frontiers in Marine Science, 2025)
Coastal wetlands play a vital role in shoreline protection, material cycling, and biodiversity conservation. Utilizing hyperspectral remote sensing technology for wetland monitoring can enhance scientific management of these ecosystems. However, the complex water-land interactions and vegetation mixtures in wetlands often lead to significant spectral confusion and complicated spatial structures, posing challenges for fine classification. This paper proposes a novel hyperspectral image classification method that combines the strengths of Convolutional Neural Networks (CNNs) for local feature extraction and Transformers for modeling long-range dependencies. The method utilizes both 3D and 2D convolution operations to effectively capture spectral and spatial features of coastal wetlands. Additionally, dual-branch Transformers equipped with cross-attention mechanisms are employed to explore deep features from multiple perspectives and model the interrelationships between various characteristics. Comprehensive experiments conducted on two typical coastal wetland hyperspectral datasets demonstrate that the proposed method achieves an overall accuracy (OA) of 96.52% and 85.72%, surpassing other benchmarks by 1.0-8.64%. Notably, challenging categories such as mudflats and mixed vegetation area benefit significantly. This research provides valuable insights for the application of hyperspectral imagery in coastal wetland classification.